Theoretical Foundations of Investments: Place in The Economy, Social Role (The Peerian Journal, 2023)
This article discusses the concept of investment in economic theory and its theoretical foundations. In the Western literature, the first attention is paid to the stock markets and stock exchanges, because in the leading developed countries, investments are mainly made in the form of securities. It is quite difficult to give a single and complete tariff to the concept of investment. Below are several definitions of the term “Investment” based on existing literature. Opinions were also expressed about the content of investments in economic sciences and various aspects of practical activity, as well as their specific characteristics